Answer:
u′ = v eq. 1
v′ = -2v -2u eq. 2
Step-by-step explanation:
We are given a second order equation of the form
u′′ + 2u′ + 2u = 0
We have to convert it into a system of first order equations.
Let
u′ = v eq. 1
Then
u′′ = v′
so
(v′) + 2(v) + 2u = 0
v′ + 2v + 2u = 0
v′ = -2v -2u eq. 2
Hence the two first order equations are
u′ = v eq. 1
v′ = -2v -2u eq. 2
We can also write these equations in matrix form as
d/dt(X) = AX
[tex]\frac{d}{dt} \left[\begin{array}{ccc}u\\v\end{array}\right] = \left[\begin{array}{ccc}0&1\\-2&-2\end{array}\right] \left[\begin{array}{ccc}u\\v\end{array}\right][/tex]
Where X is the column vector and A is the square matrix (2x2)